Analysis of the metabolic profile and comorbidities in women with endometriosis before and after surgical treatment - Lavor, Claruza Braga Holanda; Viana Júnior, Antonio Brazil; Medeiros, Francisco das Chagas (Journal of Health & Biological Sciences, 2024)
Aim: this study aimed to evaluate the effects of surgical treatment for endometriosis on the metabolic profile of women diagnosed with deep endometriosis. Methods: we conducted a prospective observational study with a sample of 30 women in the menacme diagnosed with deep endometriosis who underwent videolaparoscopic surgery in a reference center in Brazil between October 2020 and December 2021. A total of 30 women performed clinical and laboratory tests regarding their metabolic profile on two occasions, during preoperative tests and six months after video-laparoscopy. Results: patients had lower average levels of Total Cholesterol (TC), Low-Density Cholesterol (LDL-c), Triglycerides (TGC), and Fasting Glycemia (FG) after the surgical procedure. The average TC level was 8.2% lower after surgery, LDL-c was 12.8% lower, TGC was 10.9% lower, and FG was 7.3% lower. The results showed a statistically significant difference for all these parameters (p < 0.001). Conclusions: video-laparoscopy was associated with a favorable lipid profile compared to the preoperative lipid profile, with a significant improvement in the average levels of LDL-c, HDL-c, TC, TGC, and FG. Long-term follow-up studies are needed to determine whether surgical treatment for endometriosis can improve the metabolic parameters of women with endometriosis and favor a lower predisposition to atherogenesis.